A retrospective analysis of the impaction status of mandibular third molars as a risk factor for fractures of angle or condylar region of the mandible - Aya Al-Harbawee; Tauseef Ahmed; Siddiq Ahmed; Christopher Avery; Rihab Fagiry; Hafizah Amer Hamzah; Farooq Afzaal; Aqib Khan; Manish Mair; Muhammad Ali; Faizan Farid (Elsevier, 2021)
Background: The position and angulation of mandibular third molars (M3) have been found to influence the angle and condylar fractures. Due to variation in the results of relevant studies, this relationship remains not fully understood. Objective: To identify the association between the depth and angulation of M3 and the risk of fracture of the mandibular angle and condyle. Methodology: A total of 527 patients were assessed from January 2012 to June 2020. Study variables included the presence, position and angulation of M3. The outcome variables were angle and condylar fractures. Results: Mean age was 28.5 years with 93.2% (n = 499) were male. Angle fractures were significantly more frequent with an impacted M3 (p = 0.023) whereas condylar fractures were more commonly associated with a fully erupted M3. The highest incidence of angle fractures was observed with M3 classified as class II (p = 0.026) and position B (p = 0.05). In contrast, class I M3 were more frequently associated with condylar fractures. With regards to the angulation, M3 between 80° - 100° were highly correlated with angle fractures (p = 0.020) whereas M3 angulations of 60° - 80° were related to condylar injuries (p = 0.025). Conclusions: Fractures of the mandibular angle were significantly associated with Class II and position B wisdom teeth whereas class I were associated with fracture of the condyles. The likelihood of angle and condylar fractures almost doubled when M3 angulations were (80ᵒ-100ᵒ) and (60ᵒ-80ᵒ) respectively.